Active optical systems on basis of CuBr lasers with high pulse repetition rates; Atomic and Molecular Pulsed Lasers - Evtushenko G. S. Gennady Sergeevich; Gubarev F. A. Fedor Aleksandrovich; Sukhanov V. B. Viktor Borisovich; Shiyanov D. V. Dmitry Valeryevich; Torgaev S. N. Stanislav Nikolaevich; Trigub M. V. Maksim Viktorovich (2009, 2009)
В фонде НТБ ТПУ отсутствует